OCCURRENCE OF PROTEINACEOUS MOIETIES IN S- AND O-RICH LATE TITHONIAN KEROGEN (KASHPIR OIL SHALES, RUSSIA) - Mongenot T.; Riboulleau A.; Garcette-Lepecq A.; Derenne S.; Pouet Y.; Baudin F.; Largeau C. (My University, 2001)
The polar fraction, isolated from the off-line pyrolysate at 400°C of a Late Tithonian, sulphur- and oxygen-rich, kerogen was examined via Raney Nickel desulphurization and TMAH thermochemolysis. Important information on this kerogen, not accessible via conventional pyrolysis, was thus obtained: (i) its structure is not simply based on alkyl skeletons cross-linked by ether and (poly)sulphide bridges, (ii) TMAH thermochemolysis afforded direct evidence of the survival of proteinaceous moieties in this 140 million years old kerogen and (iii) encapsulation within an aliphatic organic matrix was probably the main pathway reponsible for such a conspicuous preservation, also possibly favoured by the presence of numerous sulphur links.
Keywords: SULPHUR- AND OXYGEN-RICH KEROGEN; TMAH THERMOCHEMOLYSIS; AMINO ACIDS; ENCAPSULATION